Strategic development of higher education in Kazakhstan Tasks . (Journal of Economic Research & Business Administration, 2015)
The article examined the relationship between the development of higher education of Kazakhstan and technological development of the country.Analyzes strategic objectives and development problemsnational higher education .
Keywords: higher education; challenges and problems